2012
DOI: 10.1371/journal.pone.0048243
|View full text |Cite
|
Sign up to set email alerts
|

An Intrinsically Disordered Region of the Acetyltransferase p300 with Similarity to Prion-Like Domains Plays a Role in Aggregation

Abstract: Several human diseases including neurodegenerative disorders and cancer are associated with abnormal accumulation and aggregation of misfolded proteins. Proteins with high tendency to aggregate include the p53 gene product, TAU and alpha synuclein. The potential toxicity of aberrantly folded proteins is limited via their transport into intracellular sub-compartments, the aggresomes, where misfolded proteins are stored or cleared via autophagy. We have identified a region of the acetyltransferase p300 that is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 62 publications
(96 reference statements)
1
26
0
Order By: Relevance
“…Kirilyuk et al 72 identified a highly disordered region of the acetyltransferase p300 with characteristics similar to those of prion-like domains. This region provides an interface with which misfolded proteins (including p53) can interact and aggregate.…”
Section: Molecular Partners Involved In P53 Aggregationmentioning
confidence: 99%
“…Kirilyuk et al 72 identified a highly disordered region of the acetyltransferase p300 with characteristics similar to those of prion-like domains. This region provides an interface with which misfolded proteins (including p53) can interact and aggregate.…”
Section: Molecular Partners Involved In P53 Aggregationmentioning
confidence: 99%
“…Regarding the latter, it has been recently shown that aggregation of proteins such as Tau, α-synuclein and p53, also termed as intrinsically disordered proteins (IDPs), is able to trigger a cytotoxic response associated with proteasome inhibition. IDPs may also promote aberrant interactions with other proteins, leading to diversion from their functional sites and sequestration into aggregates, thereby enhancing their cytotoxic potential [64,65]. In this context, aggregating intrabodies such as 353-anti-HP1β, anti-CD, anti-Ras and anti-E6 viral protein [8,11,66] could act as IDPs, inducing cell death through co-aggregation and accumulation of crucial proteins and consequent engulfment of the ubiquitin-proteasomal system.…”
Section: Discussionmentioning
confidence: 99%
“…This region encoded as an alternative splicing variant independent of the acetyltransferase domain provides an interaction interface for various misfolded proteins, thereby promoting their aggregation. The HAT p300 enhanced the aggregation of misfolded proteins in cell models and in LBs of PD patients containing α-synuclein [35]. It is noteworthy that the expression of human wild-type α-synuclein at physiological levels in dopaminergic neuronal cells resulted in an isoform-dependent transcriptional suppression of PKCδ, a key oxidative stress-sensitive kinase [36].…”
Section: Epigenetic Modulation In Familial Parkinson's Diseasementioning
confidence: 99%
“…Significantly lower PGC1-α levels are reported in post-mortem PD SNpc neurons, and these lower levels are associated with a loss of mitochondrial function due to a reduction in mitochondrial biogenesis [34]. A recent study identified a region of the HAT p300 that is highly disordered and displays similarities to prionlike domains [35]. This region encoded as an alternative splicing variant independent of the acetyltransferase domain provides an interaction interface for various misfolded proteins, thereby promoting their aggregation.…”
Section: Epigenetic Modulation In Familial Parkinson's Diseasementioning
confidence: 99%